APRIMORAMENTO DE TECNOLOGIAS PARA ELABORAÇÃO DE PRODUTOS DERIVADOS DE SOJA E LEITE COM PROBIÓTICOS - FIORENTINI, ÂNGELA M.; KLAJN, VERA M.; CUNHA, MÁRCIO F.; BALLUS, CRISTIANO A.; OLIVEIRA, MARLON L. D. (Salão do Conhecimento, 2013)
Resumo